AB0499 ABNORMALITY OF PERIPHERAL LYMPHOCYTE SUBSETS IN BECHET'S DISEASE AND EFFECTS OF NEW IMMUNOREGULATORY COMBINATION THERAPIES ON THESE CELLS. (2nd June 2020) - Su, Q. Y.; Zhang, S. X.; Hao, L. M.; Yang, J. Y.; Bai, J.; Guo, S. J.; Luo, J.; Liu, G. Y.; Gao, C.; LI, X.
Abstract : Background: Bechet's disease (BD) is a chronic multisystemic vasculitis. Although its exact etiopathology is unknown, both autoimmune imbalances associated with genetic and abnormal immune response of effector lymphocytes promoted by infectious factors are suggested 1 . The increase of effector T cells (Teffs) and the decrease of regulatory T cells (Tregs) are possibly the involving factors in the pathogenesis of BD 2 . Importantly, we have developed new immunoregulatory combination therapies trying to restore the reduction of Tregs in rheumatic patients. Objectives: To examine abnormal levels of lymphocyte subsets in BD patients at a relatively large-sample size and to investigate whether the immunoregulatory combination therapies have therapeutic efficacy in BD. Methods: Total 384 BD patients and 206 healthy controls (HCs) were enrolled in this cross-sectional study. Proportions and absolute numbers of peripheral T, B, NK, CD4 + T, CD8 + T, Th1, Th2, Th17 and Treg subsets were analyzed by flow cytometry (FCM) for all participants. Among these patients, 183 cases of BD patients were treated with immunoregulatory combination drugs (IMiDs) such as low-dose interleukin-2, rapamycin, metformin, retinoic acid and coenzyme Q10. The levels of peripheral lymphocyte subsets were measured before and after the treatment. Compared-T test was used to compare continuous measures and to assess effect of these drugs. Results: Compared to HCs, the absolute numbers of various Teffs such as T, B, CD4 + T, CD8 + T, Th1 and Th17 cells were significantly increased in BD group ( P <0.01), while the level of Tregs in patients with BD was severely decreased ( P < 0.05), resulting in increased ratios (imbalance) of Th1/Tregs, Th2/Tregs and Th17/Tregs ( P < 0.05) (Figure 1 ). After the IMiDs treatment, the levels of NK, CD4 + T, CD8 + T, Th1, Th17 cells as well as Tregs were significantly increased ( P <0.05). But the increased Tregs was much more dramatical than those of Teffs, resulting in a decrease in ratios of Teffs/Tregs such as Th2/Tregs ( P < 0.001) (Figure 2 ). Conclusion: Impaired balance of pro- and anti-inflammatory immune cells, especially insufficiency of Tregs, might be a cornerstone of the pathogenesis of BD. Immunoregulatory combination therapies could promote the proliferation and functional recovery of Tregs in patients with BD and might help to alleviate disease activity. References: [1]Yazici H, Seyahi E, Hatemi G, et al. Behcet syndrome: a contemporary view. Nat Rev Rheumatol 2018;14(2):107-19. doi: 10.1038/nrrheum.2017.208 [published Online First: 2018/01/04] [2]Rosenzwajg M, Lorenzon R, Cacoub P, et al. Immunological and clinical effects of low-dose interleukin-2 across 11 autoimmune diseases in a single, open clinical trial. Ann Rheum Dis 2019;78(2):209-17. doi: 10.1136/annrheumdis-2018-214229 [published Online First: 2018/11/26] Acknowledgments: None Disclosure of Interests: None declared